2009
DOI: 10.1038/ajh.2009.184
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial on Effects of the Transcendental Meditation Program on Blood Pressure, Psychological Distress, and Coping in Young Adults

Abstract: Background Psychological distress contributes to the development of hypertension in young adults. This trial assessed the effects of a mind–body intervention on blood pressure (BP), psychological distress, and coping in college students. Methods This was a randomized controlled trial (RCT) of 298 university students randomly allocated to either the Transcendental Meditation (TM) program or wait-list control. At baseline and after 3 months, BP, psychological distress, and coping ability were assessed. A subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(85 citation statements)
references
References 38 publications
4
80
0
1
Order By: Relevance
“…Not long ago, this journal published a report of a randomized, controlled trial that tested whether blood pressure (BP) could be reduced with a meditation program. 1 Those receiving meditation were observed to have a mean reduction in systolic BP (SBP) of 2.0 mm Hg compared to a 0.4 mm Hg rise for controls that was not statistically significant (P = 0.15). In a subset at higher risk for hypertension, there was a statistically significant difference in mean change of 6.3 mm Hg between the groups (P = 0.014).…”
Section: State Of the Artmentioning
confidence: 93%
“…Not long ago, this journal published a report of a randomized, controlled trial that tested whether blood pressure (BP) could be reduced with a meditation program. 1 Those receiving meditation were observed to have a mean reduction in systolic BP (SBP) of 2.0 mm Hg compared to a 0.4 mm Hg rise for controls that was not statistically significant (P = 0.15). In a subset at higher risk for hypertension, there was a statistically significant difference in mean change of 6.3 mm Hg between the groups (P = 0.014).…”
Section: State Of the Artmentioning
confidence: 93%
“…BAM research also has lacked efficacious objective measure of adherence to BAM practice sessions outside of the classroom or clinic, effecting the true reported dosage conditions (17,(24)(25)(26). The actual amount of BAM dosage is unknown in many studies and may partially contribute to the substantial heterogeneity in individuals' BP changes observed within and across trials.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of large groups of TM practitioners suggest decreased usage of medical services [9,10]. Randomised, controlled studies on TM have shown statistically significant reductions in depression compared with control groups [11][12][13][14][15][16]. One meta-analysis showed a reduction in trait anxiety and another showed an increase in self-actualisation with effects significantly larger for TM than that for other relaxation and Table 3 Outcome measures before 3-6 days of treatment at the Maharishi Ayurveda Health Centre, Norway, and after 24 months follow-up in a group learning and practicing TM and in a control group not learning or practicing TM *p<0.05; **p<0.01; ***p< 0.005 (Mann-Whitney U test, TM group compared with the non-TM control group) A very good, B good, C bad meditation programs [17,18].…”
Section: Discussionmentioning
confidence: 99%